PERBANDINGAN ENTREPRENEUR INTENTION PADA MAHASISWA MANAJEMEN UNIVERSITAS MUHAMMADIYAH GRESIK - Ichnatul Khabibah (JURNAL MANAJERIAL, 2017)
The purpose of this research is to identify the difference entrepreneur intention college student management 2012-2013 and college student management 2013-2014 and identify the influence need for achievement, norma subjective, self-efficacy, and innovation variable, that was entrepreneur intention. This research used 167 respondents as samples. Primer data were used in this research. This research tested four independent variables, need for achievement, norma subjective, self-efficacy, and innovation variable, that was entrepreneur intention. This research is also to find out the effect of the difference entrepreneur intention college student management 2012-2013 and college student management 2013-2014 and the influence need for achievement, norma subjective, self-efficacy, and innovation variable, that was entrepreneur intentionby using mann-whitney u test and two-way linear regression method. The result of the research showed that no difference entrepreneur intention college student management 2012-2013 and college student management 2013-2014 and need for achievement, norma subjective, self-efficacy significantly affect entrepreneur intention, but innovation no significantly affect entrepreneur intention.